Derivation of optimum operating conditions for the slow pyrolysis of Mahua press seed cake in a fixed bed batch reactor for bio–oil production. Issue 4 (August 2017) - Dhanavath, Kotaiah Naik; Shah, Kalpit; Bankupalli, Satyavathi; Bhargava, Suresh K.; Parthasarathy, Rajarathinam
Highlights: The optimal conditions for pyrolysis of Mahua Press Seed Cake were derived. A Response Surface Methodology (RSM) was employed in this work. The bio–oil yield was found to be affected mainly by the reaction temperature. The highest bio–oil yield was achieved at 475 °C and 45 min of retention time. Abstract: The effect of pyrolysis temperature, retention time and inert gas (i.e. N2 ) flow rate on the conversion of Mahua Press Seed Cake (PSC) into bio–oil was studied in a slow pyrolysis fixed bed batch reactor. The optimum operating conditions for the process were derived using a Response Surface Methodology (RSM). It was found that the highest bio–oil yield (49.25 wt.%) can be achieved at a moderate temperature of 475 °C and a retention time of 45 min. As expected, the bio–oil yield was found to be affected by the reaction temperature. In a GC–MS analysis of the bio–oil, major compounds found were 6–octadecenoic acid, octadecanoic acid and free fatty acids (FFAs). The physicochemical properties of a raw PSC and bio–char were studied using bomb calorimeter, elemental analysis, and Fourier Transform Infrared (FT–IR) spectroscopy techniques. The heating value of the pyrolytic bio–oil (31.53 MJ/kg) at 475 °C was found to be increased by 46% compared to that of raw PSC (21.592 MJ/kg). The FT–IR analysis indicates that there was a decrease in the number of OH (hydroxyl), CH (alkanes) and CO (primary alcohol) groups and an increase in the number of CC (aromatics) functional groups with an increase in the pyrolysis temperature. Bio–gas analysis confirmed that, at higher temperatures, higher gas yield with increased CO and CH4 contents was observed. Finally, from the energy balance and economic analysis, it has been confirmed that at the derived optimum operating conditions it is feasible to produce bio–oil from Mahua PSC.